2019
DOI: 10.1051/0004-6361/201833997
|View full text |Cite
|
Sign up to set email alerts
|

Gas flow around a planet embedded in a protoplanetary disc

Abstract: Context. The ubiquity of short-period super-Earths remains a mystery in planet formation, as these planets are expected to become gas giants via runaway gas accretion within the lifetime of a protoplanetary disc. Super-Earths' cores should form in the late stage of the disc evolution to avoid runaway gas accretion. Aims. The three-dimensional structure of the gas flow around a planet is thought to influence the accretion of both gas and solid materials. In particular, the outflow in the mid-plane region may pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 40 publications
9
50
0
Order By: Relevance
“…A key feature obvious in this figure is that the mass flow is oriented toward the core at high latitudes and away from the core in the equatorial plane. Every simulation presented in this paper displays such a global circulation, with the same orientation -outflow near the equatorial plane -as found by, e.g, Bate et al (2003), Fung et al (2015), Lambrechts & Lega (2017), Kuwahara et al (2019). The isodensity contours are pinched toward the core near the poles and outward in the equatorial plane.…”
Section: Flow Structuresupporting
confidence: 71%
See 1 more Smart Citation
“…A key feature obvious in this figure is that the mass flow is oriented toward the core at high latitudes and away from the core in the equatorial plane. Every simulation presented in this paper displays such a global circulation, with the same orientation -outflow near the equatorial plane -as found by, e.g, Bate et al (2003), Fung et al (2015), Lambrechts & Lega (2017), Kuwahara et al (2019). The isodensity contours are pinched toward the core near the poles and outward in the equatorial plane.…”
Section: Flow Structuresupporting
confidence: 71%
“…This complicates the interpretation of the changes that occur as m c is varied, something that we do naturally here and in Paper I using a single setup for all values of m c . A notable exception is the recent study by Kuwahara et al (2019), who similarly explored the divide between subthermal and super-thermal mass cores using a single 3D isothermal numerical setup. The focus of their study was on exploring the evolution of the characteristics of the midplane outflow as m c was varied; in particular, they demonstrated a significant role played by the midplane outflow in preventing the accretion of solids by the core.…”
Section: Transition From Sub-thermal To Super-thermal Mass Regimesmentioning
confidence: 99%
“…7a, b, e, and f). Since the planet chiefly perturbs the surrounding disk gas at a scale that is typically the smaller of the two when comparing the Bondi and Hill radii (Kuwahara et al 2019), the difference between UP-m001-hw01 and PI-Stokes-m001-hw01 cases can be seen in the region close to the planet. In particular, the accretion window is wider in the planet-induced gas flow than in the unperturbed flow when St = 10 −3 (Figs.…”
Section: Pebble Accretion In 2dmentioning
confidence: 99%
“…Recent hydrodynamical simulations have revealed that a planet embedded in a protoplanetary disk induces gas flow with a complex three-dimensional (3D) structure (Ormel et al 2015;Fung et al 2015Fung et al , 2019Lambrechts & Lega 2017;Cimerman et al 2017;Kurokawa & Tanigawa 2018;Kuwahara et al 2019;Béthune & Rafikov 2019). The anterior-posterior horseshoe flows extending in the orbital direction of the planet have a characteristic vertical structure that resembles a column.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 2014), the continual recycling of the accreting gas around the planet (e.g. Ormel et al 2015;Cimerman et al 2017;Kurokawa & Tanigawa 2018;Kuwahara et al 2019), the delay of gas accretion by polluted envelopes (Brouwers & Ormel 2020), and disk dissipation (Ikoma & Hori 2012;Hori & Ogihara 2020). We have recently proposed the possibility of suppressing envelope accretion via a limit due to the disk accretion rate (Ogihara & Hori 2018), and similar solutions have been discussed in other studies (e.g.…”
Section: Introductionmentioning
confidence: 70%